Teachers' Professionalism in Increasing the Creativity of Memorizing the Qur'an Students at the Al-Ashriyyah Hijir Ismail Islamic Boarding School, Bogor Regency - Irwansyah, Irwansyah; Sastradiharja, EE Junaedi; MS, Farizal (Jurnal Global Ilmiah, 2025)
In general, this research aims to analyze teacher professionalism in increasing the creativity of students in memorizing the Al-Qur'an at the Al Ashriyyah Hijir Ismail Islamic Boarding School, Bogor Regency. Teacher professionalism is one of the key factors in the success of the tahfizh learning process, especially in motivating students to be more creative in memorizing. This research uses a descriptive qualitative approach by collecting data through interviews, observation and documentation.First, the digitization of the education system has a role in shaping the character of students in the Plus Pewaris Peradaban Junior High School which is very effective in improving the character of students. This can be proven from the increase in student discipline, honesty, responsibility, being able to work fast, diligent character, working carefully, having self-confidence and increasing noble character. The results of the research show that the professionalism of teachers at the Al Ashriyyah Hijir Ismail Islamic Boarding School has a significant role in increasing the creativity of students. Teachers apply various memorization methods such as tikrar (repetition), talqin (guidance), as well as visual and auditory techniques that are adapted to the students' individual needs. Professional teachers are also able to provide more personalized guidance, as well as motivate students through learning innovations that are creative and relevant to current developments. Apart from that, the challenges faced in increasing teacher professionalism include the need for continuous training, the use of technology in learning, and increasing collaboration between teachers to create a more conducive and innovative learning environment. Based on the findings of this research, it can be concluded that teacher professionalism plays an important role in creating students who are not only able to memorize the Al-Qur'an well, but also have high creativity in the memorization process.